The Gateway of tomorrow: modernist town planning on Cape Town's Foreshore 1930-70 - Botha , Nicholas Michiel (Department of Historical Studies, 2014)
Cape Town's Foreshore has been a site of contestation for much of the twentieth century. Conventional accounts of its history describe the sudden reclamation of land in 1937, and subsequent planning throughout the 1940s and 50s. However, these accounts do not take into account the complex nature of these developments. South African urban history has tended to view town planning as an apartheid spatial practice – highlighting an over-emphasis on race that has tried to make a case for 'South African exceptionalism'. This thesis attempts to fill the lacuna on histories of Cape Town, providing a comprehensive, indepth narrative of the development of the Foreshore, and its subsequent impact on most of Cape Town's built form – the most infamous of these are the 'lost highways' of the Table Bay flyovers. It will also challenge the dominant narrative of South African planning belonging to the Corbusian tradition, instead arguing that there is a clear convergence of the City Beautiful movement with that of High Modernism. In attempting to understand the complex forces that shaped Cape Town, a thorough understanding of the particular context of the early twentieth century and the debates around town planning and the reconstruction of cities is essential. These had a direct influence on the contested visions of the city that were advocated by the Cape elite, and were influenced by British and American ideas of town planning and architecture, negotiated in a local context, and employed by a variety of actors that came from both local and international contexts. These networks of ideas highlight the transnational influence of town planning as it plays out on the Foreshore. Through the particular South African context of the time, the space of the Foreshore became layered with a political ideology that affirmed white South African ownership of the space and marked the rise of Afrikaner nationalism and capital. This 'Afrikanerisation' of the Foreshore will be shown in the various commemorative events, naming practices, monuments and buildings that arose on this contested space. This will also highlight the recurring contestations and negotiations between local (City Council) and national (South African Railways and Harbours) authorities.